Escolhas estratégicas e guerra fiscal: competição ou cooperação no caso do Estado do Rio de Janeiro - Mello, Eduardo Duprat Ferreira de (2008)
This study aims to analyze the current tendencies towards cooperation or competition among the Brazilian States in the predatory games to attract private investments. We investigate the process of building agendas, related to the alternatives of the State, while the tax reform and the end of 'biddig war' are at discussion. The research presents the historical reasons for the competition, and brings to focus the strategic conditions in which the State Government of Rio de Janeiro may join this political agenda. The results show that, without the overturn of several weaknesses in the national federative framework and the tax system, even with strong political leaderships and regulatory instruments, the competitive game among the states will not reach, in the short or medium run, a safety pattern.